2008
DOI: 10.1088/0004-637x/690/1/610
|View full text |Cite
|
Sign up to set email alerts
|

The Dust-Unbiased Cosmic Star-Formation History From the 20 Cm Vla-Cosmos Survey

Abstract: We derive the cosmic star-formation history out to z = 1.3 using a sample of ∼350 radio-selected star-forming (SF) galaxies, a far larger sample than those in previous, similar studies. We attempt to differentiate between radio emission from active galactic nuclei and SF galaxies, and determine an evolving 1.4 GHz luminosity function (LF) based on these VLA-COSMOS SF galaxies. We precisely measure the high-luminosity end of the SF galaxy LF (star-formation rate 100 M yr −1 ; equivalent to ultra-luminous IR gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
181
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(213 citation statements)
references
References 53 publications
31
181
1
Order By: Relevance
“…Dark blue triangles represent the SFR density estimated by Seymour et al (2008) using deep radio observations. Green circles represent the SFR density estimated by Smolčić et al (2009) using deep 20 cm observations and dark blue squares represent the relative contribution of ULIRGs to this SFR density.…”
Section: Discussionmentioning
confidence: 99%
“…Dark blue triangles represent the SFR density estimated by Seymour et al (2008) using deep radio observations. Green circles represent the SFR density estimated by Smolčić et al (2009) using deep 20 cm observations and dark blue squares represent the relative contribution of ULIRGs to this SFR density.…”
Section: Discussionmentioning
confidence: 99%
“…10). Measured SFR densities were taken from the compilation by Behroozi et al (2013), which includes Hα (Sobral et al 2012;Tadaki et al 2011;Shim et al 2009) radio (1.4 GHz; Karim et al 2011;Dunne et al 2009;Smolčić et al 2009), combined ultraviolet/infrared (Gruppioni et al 2015;Cucciati et al 2012;Kajisawa et al 2010;Salim et al 2007;Zheng et al 2007), ultraviolet data only (Bouwens et al 2012;Robotham & Driver 2011;van der Burg et al 2010;Yoshida et al 2006), and far infrared data only (Rujopakarn et al 2010;Le Borgne et al 2009). The default model is in good agreement with observation at z > 2 (especially with UV data) because it has strong feedback that suppresses star formation but forms too many stars at low z (Figs.…”
Section: Star Formation Ratesmentioning
confidence: 99%
“…In the past decade it has been demonstrated that a panchromatic, X-ray to radio, observational approach is key to develop a consensus on galaxy formation and evolution (e.g., Dickinson et al 2003;Scoville et al 2007;Driver et al 2009Driver et al , 2011Koekemoer et al 2011;Grogin et al 2011). In this context, the radio regime offers an indispensable window toward star formation and supermassive black hole properties of galaxies as radio A&A 602, A1 (2017) continuum emission i) provides a dust-unbiased star formation tracer at high angular resolution (e.g., Condon 1992;Haarsma et al 2000;Seymour et al 2008;Smolčić et al 2009b;Karim et al 2011); and ii) directly probes those active galactic nuclei (AGN) that are hosted by the most massive quiescent galaxies and deemed crucial for massive galaxy formation (e.g., Croton et al 2006;Bower et al 2006;Best et al 2006;Evans et al 2006;Hardcastle et al 2007;Smolčić et al 2009aSmolčić et al , 2015Smolčić 2009;Smolčić & Riechers 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These past surveys have shown that deep observations at high angular resolution ( 1 ) with exquisite panchromatic coverage are critical to comprehensively study the radio properties of the main galaxy populations, avoiding cosmic variance with large area coverage (e.g., Padovani et al 2009;Padovani 2011;Smolčić et al 2008Smolčić et al , 2009bSmolčić 2009;Smolčić & Riechers 2011;Seymour et al 2008;Bonzini et al 2012Bonzini et al , 2013. In this context, large area surveys down to unprecedented depths are planned with new and upgraded facilities (e.g., VLA, Westerbork, Australian Square Kilometre Array Pathfinder, MeerKAT, and Square Kilometre Array; e.g., Jarvis 2012; Norris et al 2011Norris et al , 2013Norris et al , 2015Prandoni & Seymour 2015).…”
Section: Introductionmentioning
confidence: 99%